USAGE OF CANVA-BASED FLIPBOOK MEDIA IN LEARNING CREATIVE PRODUCTS AND ENTREPRENEURSHIP AT SMKN 3 SOUTH TANGERANG CITY - Amalia Puspita Putri Nugraheni; Diana Mardiyani; Rusmaini (International Journal of Economics Education Research (IJEER), 2025)
One of the challenges in teaching that teachers often face is the preparation of teaching materials that are still less than optimal, teachers only use government-produced books or videos available on Youtube. With the passage of time, information technology in the digital era has become an important component in education, offering various digital tools that can improve the quality of learning. One popular tool is Canva, a graphic design platform that makes it easy to create interesting and creative learning materials. This research focuses on the use of Canva-based Flipbooks in Creative Product and Entrepreneurship subjects. Based on the problems obtained from interviews with one of the PKWU Teachers, it aims to improve teacher competence in making teaching materials, especially digital teaching materials. This research uses a qualitative approach with descriptive methods. Research instruments include module drafts, interview sheets, observation sheets. Data analysis was conducted through data reduction, data presentation in tabular form, and drawing valid and consistent conclusions. The results of the analysis show that Canva’s features, such as templates and graphic elements, support the process of visualization and organization of information, and increase student motivation and involvement in the learning process.